Effects of the Addition of Local Microorganism Bioactivators (MOLs) to Tomato Waste and EM4 on the Composite Quality of Market Waste with Coffee Waste Source - Nurhayati, Radityazty Dahayu; Ali, Munawar (Journal La Lifesci, 2024)
Market waste that belongs to organic garbage, can be recycled into compost. The natural compounding process takes quite a while, so it requires bioactivators to speed up the compostage process. In addition to the EM4 bioactivator, bioactivators can be made by ourselves with tomato waste that called local microorganisms (MOL) of tomato waste. The carbon content of coffee amps is high enough that it can be used as a compound mixture material as a source of carbon. The study aims to analyze the influence of the addition of local microorganisms (MOL) of tomato waste and EM4 on the composite quality of the market waste with coffee amps as carbon sources. The composing process was done using a composer for 14 days. The study used nine units of trials with two treatments and one control with three repetitions. The entire parameters on both composts produced with the treatment have been in accordance with SNI 19-7030-2004 standards. In compounds with local microorganisms (MOL) of tomato waste, the average carbon content was 19,23%, nitrogen 1,19%, phosphorus 0,51%, potassium 0,35%, and the C/N ratio 16.26 with temperature 30.67°C and pH 6.93. Compared to the compound with the bioactive EM4, the average content of the carbon element was 18,48%, the nitrogen content was 1,15%, the phosphates 0,50%, the potassiums 0,31%, and the C/N ratio 16.16 with temperature 31°C and pH 6.97. The results show that local microorganisms (MOL) of tomato waste have potential as a substitute for EM4 bioactivators.